2021
DOI: 10.3390/biology10111178
|View full text |Cite
|
Sign up to set email alerts
|

Siglecs as Therapeutic Targets in Cancer

Abstract: Hypersialylation is a common post-translational modification of protein and lipids found on cancer cell surfaces, which participate in cell-cell interactions and in the regulation of immune responses. Sialic acids are a family of nine-carbon α-keto acids found at the outermost ends of glycans attached to cell surfaces. Given their locations on cell surfaces, tumor cells aberrantly overexpress sialic acids, which are recognized by Siglec receptors found on immune cells to mediate broad immunomodulatory signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 253 publications
(307 reference statements)
0
22
0
Order By: Relevance
“…The Supplementary Material for this article can be found online at: https://www.frontiersin.org/articles/10.3389/ fmed.2022.979373/full#supplementary-material SUPPLEMENTARY FIGURE 1 (a) Domain organization of CD169: CD169 belongs to the Ig-like Siglec superfamily, hence the designation Sialic acid-binding immunoglobulin-type lectins. Siglecs are a group of cell surface molecules, which can roughly be subdivided into highly conserved Siglecs, including CD169, and CD33-related Siglecs (24,70,71). CD169, being one of the largests representatives of its family, consists of 17 immunoglobulin domains, that are characteristically protruding in the peripheral extracellular space.…”
Section: Authors Contributionmentioning
confidence: 99%
“…The Supplementary Material for this article can be found online at: https://www.frontiersin.org/articles/10.3389/ fmed.2022.979373/full#supplementary-material SUPPLEMENTARY FIGURE 1 (a) Domain organization of CD169: CD169 belongs to the Ig-like Siglec superfamily, hence the designation Sialic acid-binding immunoglobulin-type lectins. Siglecs are a group of cell surface molecules, which can roughly be subdivided into highly conserved Siglecs, including CD169, and CD33-related Siglecs (24,70,71). CD169, being one of the largests representatives of its family, consists of 17 immunoglobulin domains, that are characteristically protruding in the peripheral extracellular space.…”
Section: Authors Contributionmentioning
confidence: 99%
“…Regarding our data about immune changes to corticosteroids, it is noteworthy the expression of sialic acid-binding immunoglobulin-type lectins (Siglecs) on monocyte cells. Targeting Siglecs has recently emerged as a promising therapeutic strategy in cancer [ 49 , 50 , 51 , 52 ]. In our study, we found that expression of both Siglec-3 (CD33) and Siglec-5 (CD170) increased after corticosteroid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Siglec-6 expression has been reported in AML blasts and B cells in subjects with chronic lymphocytic leukemia (CLL) [ 34 ] and mucosa-associated lymphoid tissue lymphoma [ 35 ]. As Siglec-6 mRNA and protein are not expressed in hematopoietic stem cells, they are novel targets for CAR-T-cell immunotherapy in CLL [ 20 , 23 ].…”
Section: Expression Spectrum Of Siglecs In Tumorsmentioning
confidence: 99%
“…Therapeutic targeting of the Sia-Siglec axis is promising for the treatment of tumors because Siglecs are mostly expressed in immune cells and affect the TME. Currently, monoclonal antibodies (mAbs) targeting Siglecs are applied to deplete tumor cells via passive immunotherapy [ 20 ]. Most mAbs specifically bind a target antigen and neutralize or stimulate its activity; however, newer therapeutic strategies, such as immune checkpoint inhibition, and T-cell engaging therapies, such as bispecific T-cell engaging (BiTE) single-chain antibody constructs and chimeric antigen receptor (CAR) T cells, have shown remarkable efficacy in clinical trials [ 73 ].…”
Section: Targeting Siglecs In Tumor Therapymentioning
confidence: 99%